1987
DOI: 10.2169/internalmedicine1962.26.249
|View full text |Cite
|
Sign up to set email alerts
|

Water intoxication due to excessive water intake : Observation of initiation stage.

Abstract: A patient who had experienced water intoxication despite normal renal function and normal urinary diluting ability was observed during the initiation stage of hyponatremia. Upon the excessive water intake (10 to 15 L) for several days, he developed moderate hyponatremia (121 mEq/L) and headache, an early symptom frequently seen in water intoxication. During this period, his urine was maximally dilute (50 to 60 mOsm/kg H2O), and his urinary sodium excretion increased. This report suggests that 10 to 15 L of wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Gross estimations suggest that an acute (<1 h) fluid intake around 3–4 L (~1 gallon) is enough to induce symptomatic hyponatremia in otherwise healthy individuals at rest [12,52]. Although maximal urine excretion rates allow humans to tolerate water intakes approximating 20 L per day without ill-effects [79], the actual fluid intake tolerance limit appears to be closer to 10 L per day in normal individuals [43,79]. De Wardener and Herxheimer each drank 10 L of water per day (250–500 mL every 30–60 min during waking hours) for 11 days and reported physical signs of headache, scotoma, skin coldness with pallor, and puffiness of the face [43].…”
Section: Pathologymentioning
confidence: 99%
“…Gross estimations suggest that an acute (<1 h) fluid intake around 3–4 L (~1 gallon) is enough to induce symptomatic hyponatremia in otherwise healthy individuals at rest [12,52]. Although maximal urine excretion rates allow humans to tolerate water intakes approximating 20 L per day without ill-effects [79], the actual fluid intake tolerance limit appears to be closer to 10 L per day in normal individuals [43,79]. De Wardener and Herxheimer each drank 10 L of water per day (250–500 mL every 30–60 min during waking hours) for 11 days and reported physical signs of headache, scotoma, skin coldness with pallor, and puffiness of the face [43].…”
Section: Pathologymentioning
confidence: 99%
“…A concurrent factor that upsets the free water excretion capacity, such as increased antidiuretic hormone (ADH) secretion, hyperprolactinaemia, certain medications and other factors are usually involved (Illowsky and Kirch 1988, de Leon and others 1996, Mimasaka and others 2004). Yonemura and others (1987) suggested that the production of ADH due to nausea and vomiting could be the consequence of water intoxication, rather than the cause. Additionally, in a patient suffering from chronic salt poisoning, the water preservation mechanisms are activated, particularly, the production of ADH is expected to be increased.…”
Section: Investigationsmentioning
confidence: 99%
“…Two factors could have contributed to this paradox: furosemide treatment and a temporal misbalance of the principal mediators of water and sodium excretion: ADH, aldosterone, angiotensin II and auricular natriuretic peptide. The chronic water deprivation and hypernatraemia are responsible for the initial increased ADH and decreased aldosterone and angiotensin production (Yonemura and others 1987, Guyton and Hall 1996). After the excessive ingestion of water, the volaemia is suddenly increased, further inhibiting the production of aldosterone and angiotensin and promoting the release of the auricular natriuretic peptide (Yonemura and others 1987, Guyton and Hall 1996).…”
Section: Differential Diagnosismentioning
confidence: 99%
“…13,14 NHE1 activity in VSMCs has been proposed altered in hypertension 15 and diabetes. [20][21][22] In animal studies, local [Na + ] o can decrease to 45-70 mM during hypoxia and ischaemia. During intense exercise, pH o can decrease from the physiological range around 7.4 to 7.04 17 and hyponatraemia can develop most likely due to increased water intake 18 and excessive sweating.…”
mentioning
confidence: 99%
“…19 Water intoxication can lower [Na + ] o to the range 110-125 mM. [20][21][22] In animal studies, local [Na + ] o can decrease to 45-70 mM during hypoxia and ischaemia. [23][24][25] Ischaemia also causes extracellular acidification, as illustrated by the decrease of peritoneal fluid pH to 6.7 during mesenteric ischaemia 26 and interstitial pH to 6.9 during cardiac ischaemia.…”
mentioning
confidence: 99%